2018
DOI: 10.1155/2018/2358451
|View full text |Cite
|
Sign up to set email alerts
|

S100B, Homocysteine, Vitamin B12, Folic Acid, and Procalcitonin Serum Levels in Remitters to Electroconvulsive Therapy: A Pilot Study

Abstract: Background Electroconvulsive therapy (ECT) is one of the most effective treatment options for refractory depressed patients. To date, there are only a few predictors of response. Aim The aim was to identify predictive biomarkers of remission to ECT on a molecular level. Methods 11 patients suffering from a major depressive episode—according to the Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV)—underwent 10 ECT sessions. Blood samples were taken, and the depression severity was assessed before,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…A recent meta-analysis of the 3 first studies that included 51 responders and 73 non-responders found that S100B levels at baseline were significantly elevated in responders ( Shi et al, 2020 ). These findings were similar in patients treated with electroconvulsive therapy, where higher baseline S100B levels were associated with better clinical outcome at both 5 and 30 posttreatment days ( Arts et al, 2006 ) and long-term remission time ( Carlier et al, 2010 ; Maier et al, 2018 ), although no relationship with treatment response was reported ( Kranaster et al, 2014 ). Our findings reinforce these previous data and might suggest that patients with high baseline S100B have an increase in this neurotrophic factor, which may promote the antidepressant response ( Ambrée et al, 2016 ).…”
Section: Discussionsupporting
confidence: 52%
“…A recent meta-analysis of the 3 first studies that included 51 responders and 73 non-responders found that S100B levels at baseline were significantly elevated in responders ( Shi et al, 2020 ). These findings were similar in patients treated with electroconvulsive therapy, where higher baseline S100B levels were associated with better clinical outcome at both 5 and 30 posttreatment days ( Arts et al, 2006 ) and long-term remission time ( Carlier et al, 2010 ; Maier et al, 2018 ), although no relationship with treatment response was reported ( Kranaster et al, 2014 ). Our findings reinforce these previous data and might suggest that patients with high baseline S100B have an increase in this neurotrophic factor, which may promote the antidepressant response ( Ambrée et al, 2016 ).…”
Section: Discussionsupporting
confidence: 52%
“…YB-DAO-Hu), respectively. All the assays were measured on an A0018T Microplate reader (Thermo-Fisher Scientific, USA) following the instructions of reagent suppliers [38], [39].…”
Section: Methodsmentioning
confidence: 99%
“…To control motor seizure activity, a blood pressure cuff was inflated on one extremity-usually on the right lower legbefore muscle relaxation. Study details for the pilot study have already been reported elsewhere (Kleimann et al 2015;Maier et al 2018;Müller et al 2012).…”
Section: Administration Of Ectmentioning
confidence: 99%